Deciphering the maritime diplomatic properties of Malaysia's oil and gas explorations in the South China Sea - Putra, Bama Andika (Frontiers in Political Science, 2023)
Studies in maritime diplomacy have treated the development of oil and gas explorations in the South China Sea as taken-for-granted events. On the contrary, this study argues that assessing the maritime diplomatic properties inherent in energy reserve explorations can reveal unique insights, motivations, and significance of maritime diplomatic events. It assesses Malaysia's oil and gas explorations in the Luconia Shoals, informed by the analytical framework of Le Miere's maritime diplomatic properties. Utilizing secondary data from the Asian Maritime Transparency Initiative between 2020 and 2023 related to Malaysia's oil and gas project developments in the Luconia Shoals, this article concludes that the maritime diplomatic events consist of the following characteristics: 1) pre-emptive and sustainment, underlining Malaysia's long-term plan of fulfilling the growing domestic energy demand, 2) explicitness of the messages transmitted to Chinese officials in order to repel any possibilities of adversaries misconstruing Malaysia's actions at sea, and 3) moderate kinetic effect due to the lethal weaponry at the disposal of the hard power assets deployed to handle occurring crisis. Evaluation of Malaysia's maritime diplomatic properties also reveals two worrying conclusions: 1) the existence of reactive events, which can cause disruptions at sea due to the lack of planning related to the actions taken by the Royal Malaysian Navy, and 2) asymmetrical power relations between China and Malaysia, predicted to cause China to continue its power projections at sea and aggravate Malaysian policymakers.